Comparative Analysis of Handwashing with Soap and Hand Rubbing with Handrub: Efficacy and Practical Implications among Nurses - Ogya Nugraha Magani (Trigin Institute, 2023)
Hand hygiene stands as a cornerstone in infection prevention within healthcare settings, with implications for patient safety and healthcare worker well-being. This research delves into the comparative effectiveness of two fundamental hand hygiene methods handwashing with soap and hand rubbing with handrub specifically among nurses, who play a pivotal role in the frontline defense against infectious threats. A prospective, randomized controlled trial design was employed to compare the efficacy of handwashing with soap and hand rubbing with handrub among a diverse cohort of 100 registered nurses. Randomization and allocation concealment were implemented to minimize biases. The primary outcome measure was the reduction in bacterial counts on the hands of nurses, assessed through standardized swabbing techniques and microbiological cultures at baseline, immediately post-intervention, and at follow-up intervals. The findings reveal a statistically significant superiority of hand rubbing with handrub over handwashing with soap in reducing bacterial counts among nurses. Immediate post-intervention assessments demonstrated a marked reduction in bacterial counts in the hand rubbing group, with sustained effects observed over follow-up intervals. Subgroup analyses across different clinical units and years of nursing experience consistently favored hand rubbing.